Buckling behaviour of steel column having an intermediate support - Chakraborty S.; Hora M.S.; Pathak K.K. (My University, 2025)
The present work focuses on the study of buckling behaviour of square steel column by varying the position of single intermediate support along the height of column. The analysis of long steel column of size 200 mm × 200 mm and height 10 m is carried out using finite element software (ANSYS) to obtain the position of intermediate support which provides maximum buckling load and lateral deflection of the column for different boundary conditions. The position of single intermediate support is varied by 1 m along the height of column measured from the bottom end of the column and buckling load and lateral deflection is evaluated for each position to determine the maximum value of buckling load and lateral deflection for different boundary conditions. The results of analysis are compared with Euler's theory for general end support conditions. © 2006-2017 Asian Research Publishing Network (ARPN).